2020
DOI: 10.14338/ijpt-20-00038.1
|View full text |Cite
|
Sign up to set email alerts
|

Referral Patterns and Treatment Delays in Medulloblastoma: A Large Academic Proton Center Experience

Abstract: Purpose Patient travel time can cause treatment delays when providers and families decide to seek proton therapy. We examined whether travel distance or referral pattern (domestic versus international) affects time to radiation therapy and subsequent disease outcomes in patients with medulloblastoma at a large academic proton center. Patients and Methods Children with medulloblastoma treated at MD Anderson (MDA) with a protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In terms of treatment factors, there was a significant difference between the type of treatment facility at which patients and their eventual TTI. Patients treated at community programmes received treatment sooner than those treated at academic centres, possibly due to the travel arrangements necessary for patients to be treated at larger academic centres compared with the local proximity of many community‐based programmes 15 . However, academic institutions have been shown to be the more cost‐effective option of the two, with tangible survival differences being observed at academic institutions for cancers of the head and neck, often due to additional clinical expertise 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of treatment factors, there was a significant difference between the type of treatment facility at which patients and their eventual TTI. Patients treated at community programmes received treatment sooner than those treated at academic centres, possibly due to the travel arrangements necessary for patients to be treated at larger academic centres compared with the local proximity of many community‐based programmes 15 . However, academic institutions have been shown to be the more cost‐effective option of the two, with tangible survival differences being observed at academic institutions for cancers of the head and neck, often due to additional clinical expertise 16 …”
Section: Discussionmentioning
confidence: 99%
“…Patients treated at community programmes received treatment sooner than those treated at academic centres, possibly due to the travel arrangements necessary for patients to be treated at larger academic centres compared with the local proximity of many community-based programmes. 15 However, academic institutions have been shown to be the more cost-effective option of the two, with tangible survival differences being observed at academic institutions for cancers of the head and neck, often due to additional clinical expertise. 16 The type of surgery also predicted TTI, with faster receipt of care for patients receiving local tumour excision (LTE) than WLE, the mainstay surgical treatment for MCC.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous publications on travel distances to receive PBT demonstrate the field's interest in this topic and the magnitude of travel some patients experience to receive treatment. A study conducted at the MD Anderson Cancer Center, where nearly one-third of hospital admissions are from out-of-state patients as it is a destination treatment center, found the median travel distance to receive PBT for medulloblastoma was 1008 miles [ 11 ]. Another study at the Washington University School of Medicine showed that cancer patients traveled significantly more for proton than photon therapy, with mean distances of 83.3 and 47.4 miles, respectively [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Travel distance from RT facilities has been demonstrated to be a barrier to recommended care [ 10 ]. Despite this, patients may be willing to travel long distances for PBT given the potential clinical and dosimetric advantages not available at their local radiation centers [ 11 14 ]. Patients may also be interested in proton clinical trials and may be referred by formal and informal networks for special circumstances, such as re-irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…With continued program development and outcomes monitoring during transition and after transfer, it will be important to assess the educational topics and interventions that can affect outcomes after transfer to adult providers. Recommendations for topics to be included in educational sessions with HCT based on current literature are included in Table 3 (29,33,(40)(41)(42).…”
Section: Transition Clinic Implementation Transition Focus Areas and ...mentioning
confidence: 99%